2022
DOI: 10.3390/jcm11030744
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Growth/Differentiation Factor-15 in the Aqueous Humor and Serum of Glaucoma Patients

Abstract: Dysregulated levels of growth/differentiation factor-15 (GDF15), a divergent member of the transforming growth factor-beta super family, have been found to be associated with the pathology of various diseases. In this study, we evaluated the levels of GDF15 in aqueous humor (AH) and serum samples derived from primary open-angle glaucoma (POAG) and age- and gender-matched non-glaucoma (cataract) patients to assess the plausible association between GDF15 and POAG. GDF15 levels were determined using an enzyme-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“… 23 Somewhat surprisingly, GDF-15 is upregulated in RGCs following optic nerve injury as part of a putative neuroprotective response, 24 as well as in RGCs of glaucomatous rodents 25 and human glaucoma patients. 25 , 26 In light of the contrasting actions of GDF-11 and GDF-15 on RGC differentiation, we aim to investigate the single-cell profile of these two family members in an ex vivo culture model.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Somewhat surprisingly, GDF-15 is upregulated in RGCs following optic nerve injury as part of a putative neuroprotective response, 24 as well as in RGCs of glaucomatous rodents 25 and human glaucoma patients. 25 , 26 In light of the contrasting actions of GDF-11 and GDF-15 on RGC differentiation, we aim to investigate the single-cell profile of these two family members in an ex vivo culture model.…”
Section: Introductionmentioning
confidence: 99%
“…are known; however, factors associated with the manifestation of the disease have yet to be discovered. Maddala et al addressed this lacuna by looking at the levels of growth/differential factor-15 (GDF15) in the AH and serum samples in patients with glaucoma and age-and gender-matched controls [19]. The study showed significant and important serum and AH levels of GDF15 in patients with POAG when compared to controls.…”
mentioning
confidence: 99%